2007
DOI: 10.1375/twin.10.6.848
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility of Myocardial Infarction

Abstract: The aim of this study was to determine the influence of genetic factors on the first episode of acute myocardial infarction. Probandwise concordances, tetrachoric correlations and quantitative genetic analyses of liability were applied to data drawn from the Swedish Twin Registry and the Swedish Acute Myocardial Infarction Register. All same-sexed twin pairs born between 1886 and 1958 who were alive in 1987 were included in the analyses. Our results show that concordance rates for acute myocardial infarction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…In particular, onset of CAD before age 42 years is rare and atypical. Our results are broadly consistent with previous findings on the heritability of cardiac death,11 angina,36 and MI12 in Swedish twins, and sex differences in heritability of precursors of CAD 26…”
Section: Commentsupporting
confidence: 93%
“…In particular, onset of CAD before age 42 years is rare and atypical. Our results are broadly consistent with previous findings on the heritability of cardiac death,11 angina,36 and MI12 in Swedish twins, and sex differences in heritability of precursors of CAD 26…”
Section: Commentsupporting
confidence: 93%
“…Previous twin studies have found that coronary heart disease deaths, myocardial infarction and angina pectoris have a substantial hereditary component 22 23. Most recently, advances in bioinformatics and high-throughput genomic technology have facilitated the completion of several genome-wide association studies (GWAS) to search for susceptibility genes for CAD 24.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of mean monozygotic twin discordance rates from the literature and the TwinsUK cohort for a series of common diseases, such as colon cancer and breast cancer [32], rheumatoid arthritis (RA) [33,34], osteoarthritis (OA) [35], psoriasis [36], cardiovascular disease (CVD) and myocardial infarction (MI) [37], type 1 diabetes [38,39], type 2 diabetes [38,40], autism and autism spectrum disorders (ASD) [41-44], and schizophrenia [45]. …”
Section: Disease-discordant Twin Ewasmentioning
confidence: 99%